The utility of mobile telephone recorded videos as adjuncts to the diagnosis of seizures and paroxysmal events in children with suspected epileptic seizures - Oyieke, Katherine (Department of Paediatrics and Child Health, 2022)
Background: Epilepsy is largely a clinical diagnosis based on the patient's history. Neurological examination, interictal electroencephalogram and neuroimaging can all be normal in patients with epilepsy. Making the correct diagnosis in patients with suspected epilepsy is often difficult. Studies show that some 30% of patients are incorrectly diagnosed as suffering from epilepsy. Further, the diagnosis and treatment of epilepsy is often delayed. In the majority of patients, the diagnosis of epilepsy depends on the description of the attack by a witness but the inter-observer interpretations of verbal descriptions of events can be diverse and challenging. The use of mobile phone video recordings has gained worldwide prominence in recent years, including resource limited settings. This study explores the utility of mobile phone video recordings of paroxysmal events as adjuncts in the diagnosis of epilepsy, particularly in resource poor settings where there may exist significant diagnostic delays and misdiagnoses with far reaching implications on resource allocation and poor clinical outcomes. The aim of the study is to assess the accuracy of witness and referring clinician descriptions and to determine the impact, ideally enabling earlier diagnosis and management, of the use of home video recordings i.e the accuracy and timeliness of epilepsy diagnosis in paediatrics with the aim of improving practice in our setting. The existing literature is explored to guide optimal outcomes and ethical approaches to the tool which can be adapted for the paediatric setting. Objective: This study aims at outlining the utility of home videos in the diagnosis of paediatric epilepsy, and specifically describing how home videos influence the accuracy and timeliness of epilepsy diagnosis in clinical practice. Study design: This study has several arms, firstly a literature review to establish the current body of knowledge and established common practice for this intervention. The literature review critiques if there is an accepted and normed model for the use of this tool or existing evidence to support its use beyond anecdotal practice. Further, to define the apparent advantages and potential disadvantages of the intervention and to identify and develop subsequent study questions for a future prospective arm of the study. This will include questions relating to optimal recommended models for the intervention and safe ethical practice. To further assist with this consolidation of data a convenience sampling of videos randomly sent through to the neurology department over the previous year were retrospectively reviewed to assess the nature and route of the referral, the information included, the quality of the video, any ethical or safety concerns and any subsequent change in practice. Results: Eight studies met the inclusion criteria. Methodologies varied, only three included videos of children and quality of the videos was formally scored in two. Overall the studies supported that home videos of good quality had a role in assisting in the differentiation of epilepsy from non-epileptic events, this outcome increased in the setting that history was provided and with the level of experience of the clinician. Studies did not focus on the ethics or risks of home videos and for some of the studies only a small proportion of the epilepsy client load were able to provide video material. Outcome: Data relating to the role of home video of events in children is overall lacking. There are no official guidelines recommended to families for the acquisition of good quality videos in the management and assessment of seizures. Further, the ethical implications of transfer of sensitive recorded material has not been adequately addressed for this group.